Are viroids escaped introns? - Diener, T. O. (1981)
A complex of considerable stability is possible between the 5′ end of U1 RNA and a specific nucleotide sequence of the potato spindle tuber viroid complement. Because base-pairing between the 5′ end of U1 RNA and the ends of introns is believed by some to be responsible for the precise alignment and correct excision of introns, the U1-related sequence may represent the two ends of a presumed intron ancestor of the viroid complement after circularization.